2016
DOI: 10.26874/kjif.v4i1.51
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Edukasi Terhadap Pengetahuan, Sikap, Dan Kemampuan Berkomunikasi Atas Informasi Obat

Abstract: ABSTRAKPengetahuan masyarakat tentang informasi obat akan mendukung pengobatan yang rasional agar terhindar dari kesalahan penggunaan obat (medication error), penyalahgunaan (abused), dan penggunaan obat yang salah.(misuse). Minimnya pengetahuan masyarakat tentang informasi obat dan kemampuan berkomunikasi dalam pelayanan informasi obat mendorong untuk diadakannya suatu usaha edukasi dan optimalisasi kemampuan masyarakat berkaitan dengan informasi obat. Tujuan dari kegiatan edukasi tersebut adalah untuk menduk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
4
9
0
14
Order By: Relevance
“…Based on the selected media, 80% of the extension media chose extension methods with a group or community approach. This is following the results of research by Pratiwi et al (2016) that group education is also able to increase public knowledge about drug information. Oh et al (2011) also suggested that knowledge and attitudes towards antibiotics in society play an important role in the success of the treatment process.…”
Section: The Most Effective Extension Methodssupporting
confidence: 61%
“…Based on the selected media, 80% of the extension media chose extension methods with a group or community approach. This is following the results of research by Pratiwi et al (2016) that group education is also able to increase public knowledge about drug information. Oh et al (2011) also suggested that knowledge and attitudes towards antibiotics in society play an important role in the success of the treatment process.…”
Section: The Most Effective Extension Methodssupporting
confidence: 61%
“…Based on the data seen in the frequency distribution of respondents according to education, namely elementary education as many as six respondents (40.0%), junior high school education who attended counselling the most were seven respondents (46.7%), high school education two respondents (13.3%), and education diploma 0 respondents. The same thing was expressed by Pratiwi (Pratiwi et al, 2016), that the level of education of a person or individual will affect the process and ability to think to capture new information. The latest education level in Sumberjaya Village, Cihaurbeuti District, Ciamis Regency, has the highest percentage, are junior high school education at 40.0% for pregnant women and 46.7% for breastfeeding mothers.…”
Section: Discussionmentioning
confidence: 82%
“…4 Knowledge, attitude, and action towards drug information are some indications of health behaviour. 17 Therefore, it is important to have a good and correct knowledge on DAGUSIBU as a way to support proper behaviour in practicing self-medication to enhance health quality and creates high quality health standard for the community. CBIA (Self Active Learning Way) is a student's empowerment education model to improve students' smart ability in selecting drug to allow a more effective, safe, and Advances in Health Sciences Research, volume 33 economical self-medication practice.…”
Section: Discussionmentioning
confidence: 99%